Long-term follow-up of patients undergoing decompressive hemicraniectomy for malignant stroke: Quality of life and caregiver's burden in a real-world setting - Hamamoto Filho, Pedro Tadao [UNESP]; Gonçalves, Lucas Braz [UNESP]; Koetz, Nicholas Falcomer [UNESP]; Silvestrin, Aline Maria Lara [UNESP]; Alves Júnior, Aderaldo Costa [UNESP]; Rocha, Lilian Aline [UNESP]; Módolo, Gabriel Pinheiro [UNESP]; de Avila, Marla Andréia Garcia [UNESP]; Martin, Luis Cuadrado [UNESP]; Neugebauer, Hermann; Zanini, Marco Antônio [UNESP]; Bazan, Rodrigo [UNESP] (Elsevier, 2020)
Background and Purpose: Decompressive hemicraniectomy is a life-saving procedure for the treatment of space-occupying middle cerebral artery infarctions (malignant stroke); however, patients may survive severely disabled. Comprehensive data on long-term sequelae outside randomized controlled trials are scarce. Methods: We retrospectively evaluated the survival rates, quality of life, ability to perform activities of daily living, and caregiver burden of 61 patients (aged from 37 to 83) who had previously undergone decompressive hemicraniectomy for malignant stroke between 2012 and 2017. Results: The mortality rate was higher among patients older than 60 years than among younger patients (71.0 % vs 36.7 %, p = 0.007; odds ratio 4.222, 95 % confidence interval 1.443–12.355). The mean survival time was 37.9 ± 6.0 months for 19 survivors of the younger group and 22.6 ± 5.7 months for 9 survivors of the older group. Among the 28 surviving patients, 22 (78.6 %) were interviewed, and we found that age was a determining factor for functional outcome (Barthel indices of 65.7 ± 10.6 for younger patients vs 48.0 ± 9.3 for older patients, p < 0.001), but not for quality of life. The caregiver burden was significantly correlated (R = -0.53, p < 0.01) with the severity of disability and age (R = 0.544, p = 0.011) of the patients. Conclusion: Our findings show that the degree of impairment, as well as caregiver burden, is higher in patients older than 60 years than in younger patients.
Keywords: Caregiver's burden; Decompressive hemicraniectomy; Malignant stroke; Middle cerebral artery stroke; Quality of life